A new fish species of the Genus Hapalogenys (Perciformes: Hapalogenyidae) from the Bay of Bengal, India - Mohapatra, Anil; Ray, Dipanjan; Kumar, Vikas (Zootaxa, 2013)
A new species of the genus Hapalogenys, Hapalogenys bengalensis sp. nov. is described from fourteen specimens collected from the Bay of Bengal coast. The species is distinct in having three longitudinal dark stripes; pelvic-fin tip almost reaching the base of first anal-fin spine when depressed; transverse scale rows above lateral line 7–8, below lateral line 19–20; gill rakers 18 (7 on lower limb and 11 on upper limb); posterior angle of jaw reaching vertical through anterior rim of eye. Genetic divergence (13.0–14.2%) and analysis of NJ tree shows that the new species is closely related to H. kishinouyei in the “Hapalogenys kishinouyei complex” with significant morphological difference from the other three species reported from the same complex.